Tăng cường hoạt động giám sát của Quốc hội nước ta hiện nay - Nguyễn, Văn Mạnh (2011)
Tác giả: Nguyễn Văn Mạnh, TS; Trịnh Đức Thảo; Lê Đình Hòe; Quách Sỹ Hùng; Trần Đình Thắng; Nguyễn Thị Tuyết Mai; Lê Đình Mùi; Nguyễn Cảnh Quý; Nguyễn Kim Đạt; Lê Tuấn Sơn; Mai Thị Chung; Tào Thị Quyên -- Từ khóa: Quốc hội; Hoạt động giám sát